Pelatihan Peningkatan Kapasitas Pemuda Dan Manajemen Organisasi Bina Remaja - Syamsi Mawardi; Mukrodi Mukrodi; Wahyudi Wahyudi; Endang Sugiarti; Samsul Anwar (Perhimpunan Sarjana Ekonomi dan Bisnis, 2021)
Taking part in community development is not as easy as turning your palms. This is also the case with raising youth awareness to participate in this development. Therefore, efforts are needed to awaken, motivate and guide youth in order to increase their capacity to play an active role in community development. Based on these conditions, it is an obligation for a lecturer to convey his knowledge and foster the community, especially youth, to increase their capacity through organizing youth capacity building training and organizational management. This activity explicitly aims to increase knowledge, skills and community enthusiasm for the benefit of the organization, so that organizational problems can be resolved. Scientific efforts made using a qualitative approach. Namely, providing individual capacity building training through knowledge sharing methods, sharing organizational experiences, and organizational skills practice. Participants are members of Bina Youth Rw 02 Pondok Benda Pamulang. The results of this activity indicated that the participants were very enthusiastic in studying capacity building and organizational management. This is because sharing organizational experiences can trigger enthusiasm and awareness of participants in organizing.